Different proportions of starch and neutral detergent-soluble fiber in diets for feedlot lambs - GONÇALVES,JOSEMIR S. (2022)
Abstract This study evaluated the replacement of starch (ST; cracked corn) by neutral detergent-soluble fiber (NDSF; citrus pulp) and its effects on feed intake, performance, digestibility, carcass traits, and nitrogen balance of lambs. In Experiment 1, male lambs (n = 24, 19.1 ± 1.9 kg body weight [BW]) received: Starch (ST) = 250 g starch/kg dry matter (DM); ST/NDSF = 180 g starch/kg DM + 180 g NDSF/kg DM; or NDSF = 250 g NDSF/kg DM. After 84 d, animals were slaughtered and carcasses were evaluated. In Experiment 2, male lambs (n = 15, 23.2 ± 2.3 kg BW) were used to assess digestibility and nitrogen balance. Final BW, average daily gain, gain to feed and feed intake decreased when animals were fed NDSF (P≤0.002), reflecting in lighter carcasses (P<0.0001). The NDSF decreased edible non-carcass components (P=0.0006), total usable products (P<0.0001), commercial cuts and intramuscular fat (P≤0.02). Except for NDSF and ST, the digestibility of nutrients was improved for NDSF diet (P≤0.04). The use of 250 g NDSF/kg DM as citrus pulp in finishing diets for lambs impairs performance, carcass, meat traits and nitrogen balance. However, the moderate replacement of corn by citrus pulp does not change productive variables.